Reconceptualizing the Early Bronze Age Southern Levant without Cities: Local Histories and Walled Communities of EB II–III Society. (1st June 2015) - Chesson, Meredith
Abstract : Traditionally, the Early Bronze Age (EBA) has been described as the first urban society in the southern Levant. In comparison to many other regions of the world, such as ancient Mesoamerica, North America, Europe, East Asia, and Mesopotamia, EBA society does not pass the 'urban litmus test'. In this paper I argue that ultimately the EBA evidence does not fit standard definitions of urbanism because it lacks three key elements: scale of differentiation, increased localized diversity and coherence of identity, and a rural and urban dichotomy in lifeways. Instead, I suggest that we need to analyze and reconstruct EBA society in terms of its own regional, economic, political, and social context, and work to build new ways of understanding EBA society. From the standpoint of an anthropological archaeologist, I believe that people in the EBA were working towards a societal project, a cultural endeavor, that involved population aggregation, the founding of fortified communities, intensification of agricultural and pastoral production, innovative water management and irrigation technologies, and increasingly regionalized expression of EBA (material) culture—but that this project was not an urbanizing cultural transformation. I focus on mortuary practices at two major, well-published EBA walled communities, Jericho and Bab adh-Dhra`, in order to demonstrate the lack of coherence, degree of diverse material practices, and absence of pronounced differentiation in EBA society.